Religious news as a form of mass communication: psychological markers - Kostruba, Natalia (Psychological Prospects Journal, 2020)
Purpose. The purpose of the article is to empirically determine the main psychological markers of religious news.Methods. To achieve the goal of the study, we used computer software Statistica 12 and Linguistic Inquiry and Word Count (LIWC2015). Research materials were news of the largest churches in Ukraine (Orthodox, Catholic, Protestant). All information messages for the period from 27.11.-03.12.2020. In total, 43 information messages were analyzed.Results. Prepositions, conjunctions and pronouns dominate among all categories of stylistic words. The analysis of religious news showed that most of the text concerns spatial connections (7.03%), motivators (drivers) that motivate actions (5.99%), cognitive processes (4.74%), society and social processes (2.96%), affiliation (2.17%), religious terminology (2.08%). The words "Ukrainian", "church", "temple" are most often used in religious news. The content of the news is often about celebrating significant dates or commemorating, and so on. This fact confirms the frequent use of the words "year" and "holidays". In general, religious messages call for unity, using the words "ours" and trying to unite people around Ukrainian identity. The words "authority" and "representative" are often used in religious news. Conclusions. Religious news carries out educational activities and social advertising of unity and mutual support. The unifying factors are not only the common faith, but also one nation and overcoming difficult times for the whole audience (in particular, the Covid-19 pandemic). Religious news has a great cognitive complexity of the text. Messages evaluate and discuss the present, no predictions for the future. A cross-cutting feature of all messages is the appeal to church involvement, calls to prayer and reading of religious literature. Modern religious news often mentions public authorities, emphasizing their authority.